INFLUENCE OF LEADERSHIP, HAPPINESS, INTERPERSONAL COMMUNICATION TO NORMATIVE COMMITMENT OF PUBLIC JUNIOR HIGH SCHOOL TEACHERS IN KAMPAR REGENCY OF RIAU PROVINCE - Sispurwanto, Yedi; Luddin, Muchlis R.; Fitri, Rugaiyah (JERAM, 2018)
The purpose of this study is to study the influence of leadership, happiness, interpersonal communication to normative commitment of public Junior High School teachers in Kampar Regency of Riau Province. This research uses a quantitative approach with the survey method. The sample of this research is 148 lecturers of civil servant status (PNS) at public Junior High Schools (SMP Negeri) located in Kampar Regency, which is collected from 4 schools, selected based on schools that get the highest National Examination (UN) and National Examination Integrity Index (IIUN) value at 4 sub-districts. The results of this study indicate that (1) leadership has a direct effect on the teacher's normative commitment, (2) happiness directly affects teacher's normative commitment, (3) interpersonal communication has a direct effect on teachers' normative commitment; (4) direct influence toward teacher interpersonal communication (5) happiness directly affects teacher's interpersonal communication, (6) leadership has a direct effect on teacher's happiness, so teacher's normative commitment can be improved if there is a good leadership behavior, happiness in workplace and intimacy in interpersonal communication. Especially for Kampar Regency of Riau Province, the region which is nicknamed “Riau Province' Veranda of Mecca”, to increase teachers' normative commitment is to facilitate the needs related to facilities and infrastructure, programs, activities that can improve science and practice values ​​to muslim teachers because based on the questionnaire results, the majority of teachers responded to the point that: